PENERAPAN STRATEGI ANALISIS WACANA KRITIS MODEL VANDIJK UNTUK MENINGKATKAN KEMAMPUAN MAHASISWA MENGANALISIS PROSA FIKSI DAN DRAMA - ., Gazali (Kreatif, 2014)
Abstract : The Students find difficulty when doing analysis of prose and drama in the âProsa fiksi dan dramaâ course. The difficulties caused by the lack of prior knowledge possessed by the students. In addition, the approaches used in the analysis are the traditional approach. The results of preliminary observations made in the course at the first and the second meeting found results that the average student only understand as much as 35.89 percent of the total content of prosa (novels and romance) and drama scripts.Results and discussion with the students concerning theÂ difficulties to understand the content of the discourse, is caused by: (1) an interest in reading the results of literature (prose and drama) is relatively less, (2) the time required to read prosa and drama discourse relatively long and boring), (3) the student donât have novels a that are required in the course of Prose Fiction and Drama. The reality are really concerned because that skill are required in the course regarding literature based approach. The strategy model Van Dijk Strategy used to overcome this problem.The purpose of this research is to improve and enhance the students ability to analyze prose and drama by using the strategy of Critical Discourse Analysis model of Van Dijk. This research is action research using the model of Kemmis & McTaggart. In this model, there are four stages that must be passed by the students, planning, action, observation, reflection and re-planning. The students in this research are the second semester students of Indonesian Education Program which are taking the Prose and Drama course. The number of students were at least 39 people consisting of 17 men and 22 women. Performance indicators defined in this study was 85 percent classical completeness.The results of the study found that there is an increasing in the ability of students in reviewing the novel/romance and drama scripts. In the first cycle of performance indicator reached 66.66%. The second cycle performed Because the performance has not reached 85%. The students achieved the ability to examine novel/romance and drama scripts exceed the treshold of performance indicators. The result of the second cycle reached Â 87.71%. Â Keywords: Strategy Critical Discourse Analysis Model Vandijk, Student Ability, Analysis of Prose and Drama.